1993
DOI: 10.1007/bf00312635
|View full text |Cite
|
Sign up to set email alerts
|

Genomic heterogeneity in the yeast Candida parapsilosis

Abstract: Candida parapsilosis shows a wide intraspecies variation in chromosome/homolog size distribution. As a prerequisite for delineating modes of transmission, we have undertaken an analysis of genetic variation at different levels. In the present study we have observed that a majority of isolates display similar electrophoretic karyotype patterns consistent for the species, with variations in the smaller group of chromosomes. In two strains we observed phenotypic "switching"; one of these also exhibited a mixed ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
1
2

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 19 publications
7
43
1
2
Order By: Relevance
“…We have extended the observations of Lott et al (1993) and Enger et al (2001) that phenotypic switching occurs in C. parapsilosis. We identify four core phenotypes, three of which are similar to those described by Enger et al (2001).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…We have extended the observations of Lott et al (1993) and Enger et al (2001) that phenotypic switching occurs in C. parapsilosis. We identify four core phenotypes, three of which are similar to those described by Enger et al (2001).…”
Section: Discussionsupporting
confidence: 59%
“…Switching between variant colony morphologies in C. parapsilosis was first described by Lott et al (1993) Fig. 1).…”
Section: Identification Of Colony Phenotypesmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast with C. dubliniensis, several recent studies have demonstrated a wide degree of genetic heterogeneity within C. parapsilosis [37,59,70,96,97]. Two such studies-mploying RAPD analysis, isoenzyme profile analysis and nucleotide sequence analysis of the ITS 1 internally transcribed spacer sequences flanking the 5.8s RNA gene-have detected three distinct groups among C. parapsilosis clinical isolates [37,97].…”
Section: Application Of Molecular Techniques To Resolving Anomalies Imentioning
confidence: 99%
“…Several recent surveys have described genetic and/or genomic heterogeneity among C. parapsilosis isolates (Lott et al, 1993;Branchini et al, 1994;Cassone et al, 1995;Pfaller et al, 1995;De Bernardis et al, 1999). Data from DNA-DNA reassociation, restriction length polymorphism (RFLP) and isoenzyme profiling suggest that the form species C. parapsilosis consists of the three variant groups that may even represent three distinct species (Lin et al, 1995;Roy & Meyer, 1998).…”
Section: Introductionmentioning
confidence: 99%